The linear function whose graph passes through (-4 , 0) and (1, 3) is the equation of the line passing through the two points.

The equation of the line passing through (x1 , y1) and (x2, y2) is given by (y - y1) = [(y2 - y1)/(x - x2)]*(x -...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The linear function whose graph passes through (-4 , 0) and (1, 3) is the equation of the line passing through the two points.

The equation of the line passing through (x1 , y1) and (x2, y2) is given by (y - y1) = [(y2 - y1)/(x - x2)]*(x - x1).

Substituting the values given to us we get:

(y - 0) = [( 3- 0)/(1+ 4)]*( x + 4)

=> y = (3/5)*(x + 4)

Therefore the function is

**f(x) = (3x/5) + 12/5**